Spontaneous Ovarian Hyperstimulation Syndrome with FSH Receptor Gene Mutation: Two Rare Case Reports - Emsal Pinar Topdagi Yilmaz; Omer Erkan Yapca; Yunus Emre Topdagi; Seray Kaya Topdagi; Yakup Kumtepe (Case Reports in Obstetrics and Gynecology, 2018)
Development of ovarian hyperstimulation syndrome (OHSS) is very rare in a spontaneous ovulatory cycle and it is usually seen during pregnancy. In the etiology of OHSS, higher hCG (molar pregnancies or multiple pregnancies) and thyroid-stimulating hormone (TSH) levels have been accused. In recent years, some follicle-stimulating hormone (FSH) receptor (FSHR) gene mutations have been described in patients with OHSS in the first trimester with normal hCG levels. Herein, we report two cases of FSHR gene mutation during the investigation of the etiology of spontaneous OHSS. Although OHSS is typically associated with ovulation induction, it should be kept in mind that this condition may also develop in spontaneous pregnancies.